America in Revolution - Cantwell, John, 1961- (Sydney McGraw-Hill, 2005)
Designed to meet the curriculum requirements of the Western Australian senior history syllabus and other Australian states. Comprehensive coverage of the American revolution providing visual sources such as photographs, diagrams, maps and timelines as well as letters and much more. Years 11-12.
Include Index, Maps and Illustration
Keywords: United States -- United States -- History